A sensitive and reliable detection of thrombin via enzyme-precipitate-coating-linked aptamer assay - Lee, Hye-Jin; Kim, Byoung Chan; Oh, Min-Kyu; Kim, Jungbae (ROYAL SOC CHEMISTRY, 2012)
Stable enzyme precipitate coatings (EPCs) with high enzyme loading were employed to develop a sensitive and reliable detection protocol, termed EPC-linked aptamer assay (EPC-LAA). EPC-LAA achieved the limit of detection to be 0.5 ng per mL of thrombin (13.5 pM), and maintained a reasonably stable detection signal even after storing all the reagents at 40 degrees C for 66 days.
Keywords: PROTEIN-DETECTION; NEGATIVE COOPERATIVITY